A diagnosis of Birt–Hogg–Dubé syndrome in individuals with Smith–Magenis syndrome: Recommendation for cancer screening. Issue 2 (13th December 2022) - Vocke, Cathy D.; Fleming, Leah R.; Piskorski, Anna M.; Amin, Ali; Phornphutkul, Chanika; de la Monte, Suzanne; Vilboux, Thierry; Duncan, Folami; Pellegrino, Joan; Braddock, Bonnie; Middelton, Lindsay A.; Schmidt, Laura S.; et al.
Abstract: We report a series of four unrelated adults with Smith–Magenis syndrome (SMS) and concomitant features of Birt–Hogg–Dubé (BHD) syndrome based upon haploinsufficiency for FLCN and characteristic renal cell carcinomas and/or evidence of cutaneous fibrofolliculomas. Three of the cases constitute the first known association of histopathologically verified characteristic BHD‐associated renal tumors in adults with SMS; the fourth was identified to have histologically confirmed skin fibrofolliculomas. Molecular analysis documented second‐hit FLCN mutations in two of the three cases with confirmed BHD renal pathology. These cases suggest the need to expand management recommendations for SMS to include kidney cancer surveillance starting at 20 years of age, as per the screening recommendations for BHD syndrome.